Recent Advances in Chinese Herbal Medicine for Cerebral Ischemic Reperfusion Injury - Huang, Ping; Wan, Haitong; Shao, Chongyu; Li, Chang; Zhang, Ling; He, Yu (Frontiers in Pharmacology, 2022)
Cerebral ischemic reperfusion injury (CI/RI) is a critical factor that leads to a poor prognosis in patients with ischemic stroke. It is an extremely complicated pathological process that is clinically characterized by high rates of disability and mortality. Current available treatments for CI/RI, including mechanical and drug therapies, are often accompanied by significant side effects. Therefore, it is necessary to discovery new strategies for treating CI/RI. Many studies confirm that Chinese herbal medicine (CHM) was used as a potential drug for treatment of CI/RI with the advantages of abundant resources, good efficacy, and few side effects. In this paper, we investigate the latest drug discoveries and advancements on CI/RI, make an overview of relevant CHM, and systematically summarize the pathophysiology of CI/RI. In addition, the protective effect and mechanism of related CHM, which includes extraction of single CHM and CHM formulation and preparation, are discussed. Moreover, an outline of the limitations of CHM and the challenges we faced are also presented. This review will be helpful for researchers further propelling the advancement of drugs and supplying more knowledge to support the application of previous discoveries in clinical drug applications against CI/RI.